2024
DOI: 10.1039/d3dt03532h
|View full text |Cite
|
Sign up to set email alerts
|

A rationally designed 3DTiO2@CdZnS heterojunction photocatalyst for effectively enhanced visible-light-driven hydrogen evolution

Zhuoyang Li,
Hao Ji,
Ziwen Feng
et al.

Abstract: A 3DTiO2/CZS heterojunction photocatalyst with a very high hydrogen evolution rate of 75.38 mmol h−1 g−1 under visible light was prepared for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 52 publications
(62 reference statements)
0
0
0
Order By: Relevance
“…55 The sulfur vacancies and twin heterojunctions of Cd x Zn 1−x S facilitate separation of photogenerated carriers and adsorption of S 2− , exhibiting good photocatalytic activity. 17 It has been reported that Cd x Zn 1−x S with x between 0.4 and 0.6 shows the best photocatalytic hydrogen production activity. 6 Although pure Cd x Zn 1−x S already has good photocatalytic activity, it still has the problem of short photocarrier lifetime and poor stability.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…55 The sulfur vacancies and twin heterojunctions of Cd x Zn 1−x S facilitate separation of photogenerated carriers and adsorption of S 2− , exhibiting good photocatalytic activity. 17 It has been reported that Cd x Zn 1−x S with x between 0.4 and 0.6 shows the best photocatalytic hydrogen production activity. 6 Although pure Cd x Zn 1−x S already has good photocatalytic activity, it still has the problem of short photocarrier lifetime and poor stability.…”
Section: Introductionmentioning
confidence: 99%
“…Cd x Zn 1– x S is a promising n-type semiconductor material with the advantages of adjustable band gap and edge position, simple synthesis process, and strong light absorption ability . The sulfur vacancies and twin heterojunctions of Cd x Zn 1– x S facilitate separation of photogenerated carriers and adsorption of S 2– , exhibiting good photocatalytic activity . It has been reported that Cd x Zn 1– x S with x between 0.4 and 0.6 shows the best photocatalytic hydrogen production activity .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations